Prevalence and outcomes of pediatric surgical conditions at Connaught Hospital in Freetown: a retrospective study - Naomi Wright; Emily Smith; Henang Kwasau; Cesia Cotache-Condor; Andie Grimm; Juliana Kamanda; Aiah Lebbie; Pamela Espinoza (BMJ Publishing Group, 2023)
Background Sub-Saharan Africa experiences a disproportionate amount of pediatric surgical disease, with 80% of children lacking access to timely, affordable, and safe surgical care. This study aims to characterize the burden of disease and outcomes of pediatric surgical conditions at Connaught Hospital, the main pediatric referral hospital in Sierra Leone.Methods This retrospective and hospital-based study included children up to 15 years old who were operated on between 2015 and June 2016 at Connaught Hospital in Freetown, Sierra Leone. Descriptive and inferential statistics were used to characterize the distribution of disease and compare all variables against age category and mortality.Findings A total of 215 patients were included in this study of which 72.5% (n=132) were male and 27.5% (n=50) were female. Most of the patients were diagnosed with congenital anomalies (60.9%; n=131). However, infection was the leading diagnosis (60.5%; n=23) among patients aged 5-10 years (n=38). Inguinal hernia was the leading condition (65.0%; n=85) among patients presenting with a congenital anomaly. The condition with the highest mortality was infections (17.0%; n=8), followed by other conditions (9.1%; n=2) and congenital anomalies (3.1%; n=4). Based on the results of this study, over 7000 children with inguinal hernias remain untreated annually in Freetown, Sierra Leone.Conclusion This study quantifies the burden of surgical disease among children, a foundational step toward the prioritization of pediatric surgical care in national health agendas, the development of evidence-based interventions, and the strategic allocation of resources in Sierra Leone.